2013
DOI: 10.1097/qai.0b013e3182968dda
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptability and Safety of the Shang Ring for Adult Male Circumcision in Rakai, Uganda

Abstract: Objectives Medical male circumcision (MMC) is recommended for HIV prevention in men. We assessed the acceptability and safety of the Shang Ring device compared to the dorsal slit method. Methods HIV-negative, uncircumcised men aged 18 years or older who requested free MMC services in rural Rakai, Uganda were informed about the Shang Ring and dorsal slit procedures and offered a free choice of procedure. Men were followed at 7 days postoperatively to assess adverse events (AEs) related to surgery and to remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
57
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 12 publications
11
57
3
Order By: Relevance
“…In our view, this process does not require flipping the foreskin, and there is no need to cut slits on the posterior edges of the foreskin. A non-RCT by Kigozi et al 27 reported that the mean surgical duration for SRC was 6.1 minutes, compared with 17.7 minutes for CC. Bratt and Zyambo 28 reported 13.4 minutes, on average, for SRC vs 24.3 minutes for CC.…”
Section: Adverse Event Ratementioning
confidence: 97%
“…In our view, this process does not require flipping the foreskin, and there is no need to cut slits on the posterior edges of the foreskin. A non-RCT by Kigozi et al 27 reported that the mean surgical duration for SRC was 6.1 minutes, compared with 17.7 minutes for CC. Bratt and Zyambo 28 reported 13.4 minutes, on average, for SRC vs 24.3 minutes for CC.…”
Section: Adverse Event Ratementioning
confidence: 97%
“…Another study in Uganda enrolled 621 men; among them, 508 (82%) chose SC and 113 chose CC. Results of this study demonstrated that SC is highly acceptable and safe, and could improve the efficiency of MC services [34].…”
Section: Fight Against Sexually Transmitted Infections With Scmentioning
confidence: 90%
“…To reduce overall program costs, cost saving strategies were employed including use of clinical officers (equivalent to physician’s assistants) [21] and research on use of the Shang Ring and PrePex devices, which require less time and equipment than conventional surgical procedures [22, 23]. …”
Section: Methodsmentioning
confidence: 99%